Impact of gender on leisure participation: a cross sectional study among elderly population in Malaysia - Minhat, Halimatus Sakdiah; Mohd Amin, Rahmah; Shamsuddin, K. (Community Health Society Malaysia, 2014)
Background: Leisure is a crucial aspect of life regardless of gender. This study aims to identify the different pattern of leisure involvement of elderly people in Selangor, Malaysia. Methods: A cross-sectional study was conducted among 268 elderly aged 60 years and above from 8 health centers in four different districts of Selangor. Leisure participation was measured using a validated Leisure Participation Questionnaire (LPQ), specifically validated for Malaysian elderly, consisting of 25 activities, categorized into recreational (physical), cognitive, social and productive activities. Frequency of participation for each activity was measured using a 6-point likert scale ranging from 0 to 5. Results: Overall, the patterns of leisure participation among the male and female elderly in Malaysia were almost similar. Both gender shared the same five most commonly performed leisure activities on daily basis, which were having conversations while relaxing, reading, watching television, gardening and spending time with grandchildren. Meanwhile, the most unpopular leisure activities were playing golf, performing musical instruments and playing sports with more than 90.0% of them had never performed these activities during leisure time. It was also found that only recreational (physical) activity was significantly associated with gender, with male elderly having a higher mean score (2.91±3.20) respectively. Perceived social support received from friends was found to be an important and main determinant of leisure participation for both gender. Conclusion: The lacking of physical activity involvement among female elderly and the importance role of social support from friends should be acknowledged by relevant authorities in any elderly-related programme.